ENFORCEMENT OF ADMINISTRATIVE VERDICTS - NOVELTIES AND CHALLENGES – (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
Administrative judicial protection would not achieve its essence if it is not exercised in an efficient and effective manner. We see the effectiveness through the mandatory court decisions against the plaintiff, the defendant and the interested parties. This means that the public authorities are obliged to act on the instructions expressed in the verdicts and to perform the same within the prescribed deadline, which according to the Law on Administrative Disputes is 30 days. However, in the practice of the Administrative Court, it is not uncommon for the public authorities to refrain from executing the decision reflected in the Annual Reports of the Administrative Court, in the part referring to the filed lawsuits for failure to act upon the administrative-court decision. Consequently, the regulations governing this issue will be subject to analysis in this paper. In addition, a special emphasis will be placed on the Recommendation Rec (2003) 16, which refers on the execution of administrative and judicial decisions in the field of administrative law.